2009
DOI: 10.1186/1479-5876-7-18
|View full text |Cite
|
Sign up to set email alerts
|

Generation in vivo of peptide-specific cytotoxic T cells and presence of regulatory T cells during vaccination with hTERT (class I and II) peptide-pulsed DCs

Abstract: BackgroundOptimal techniques for DC generation for immunotherapy in cancer are yet to be established. Study aims were to evaluate: (i) DC activation/maturation milieu (TNF-α +/- IFN-α) and its effects on CD8+ hTERT-specific T cell responses to class I epitopes (p540 or p865), (ii) CD8+ hTERT-specific T cell responses elicited by vaccination with class I alone or both class I and II epitope (p766 and p672)-pulsed DCs, prepared without IFN-α, (iii) association between circulating T regulatory cells (Tregs) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…Although most tumor Ags are self-Ags or modified self-Ags, intentional immunization with these Ags is conducted for therapeutic benefit. For example, class II tetramer studies in patients with malignant melanoma after experimental vaccine therapies documented evidence of immunogenicity, measured the effects of adjuvant on T cell lineage, and have been used to evaluate shifts in T cell subsets (56)(57)(58)(59). Indeed, because the pMHC complex is itself a surrogate for Ag recognition, it is feasible that tetramers might be considered for therapeutic expansion of Ag-specific effector T cells (60).…”
Section: Rare Cd4 T Cell Detection Using Class II Pmhc Tetramersmentioning
confidence: 99%
“…Although most tumor Ags are self-Ags or modified self-Ags, intentional immunization with these Ags is conducted for therapeutic benefit. For example, class II tetramer studies in patients with malignant melanoma after experimental vaccine therapies documented evidence of immunogenicity, measured the effects of adjuvant on T cell lineage, and have been used to evaluate shifts in T cell subsets (56)(57)(58)(59). Indeed, because the pMHC complex is itself a surrogate for Ag recognition, it is feasible that tetramers might be considered for therapeutic expansion of Ag-specific effector T cells (60).…”
Section: Rare Cd4 T Cell Detection Using Class II Pmhc Tetramersmentioning
confidence: 99%
“…A potential issue limiting the immune response to vaccination is the presence of regulatory T cells (Tregs) that suppress T cell activation [8], [9]. Multiple studies in mice have shown that Tregs dampen the immune response against pathogens, including S. japonicum [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…In similar studies with a telomerase peptide-pulsed DC vaccine, an antigen-specific CD8 + T-cell response was generated in patients who developed various cancers following vaccination. This response was enhanced when DCs were also pulsed with class II telomerase peptides, illustrating the importance of CD4 + T cells in fighting tumor [58]. Pulse can also be performed with peptides from multiple tumor antigens, as was performed in a Phase I clinical study by Carbone et al Patients with various cancers, including pancreatic cancer, immunized with p53 and K-Ras peptide-pulsed PBMCs saw increased survival [59].…”
Section: Whole-cell Vaccinesmentioning
confidence: 99%